Monolayer protected gold nanoparticles: theeffect of the headgroup–Au interaction - Olmos Asar, Jimena Anahí (2014)
In this work we present an atomistic simulation study analyzing the effect of ligand molecules on the morphology and crystalline structure of monolayer protected gold nanoparticles (NPs). In particular, we focused on Au NPs covered with alkyl thiolates (-SR), which form a strong covalent bond with the Au surface, and alkyl amines (-NH2R), which physisorb onto gold. The atomic interactions between gold and the head groups of ligand molecules were represented by means of a recently developed bond-order potential [Olmos-Asar et al., Phys. Chem. Chem. Phys., 2011, 13, 6500]. We found in the case of strong passivants (i.e. -SR) significant surface damage and/or amorphous-like structures, whereas soft passivants (-NH2R) do not produce almost any distortion in the crystalline structure of the metallic NPs. The enriched coverage degree related to flat surfaces is also discussed. We have also demonstrated that the new semi-empirical potential can reproduce low-coordinated adsorption sites, unlike usual pairwise classical potentials. In general, our simulations provide a direct observation of the structure of ligand protected gold nanoparticles.